Speculative Realism and Its Allure: Marketing Within Philosophy - Simon Obirek Berg (Das Questões, 2023)
In discussing the developments of speculative realism for the past fifteen years, it becomes imperative to account for even the most wayward thoughts of its supposed thinkers. In this regard, philosophy and marketing are two disparate fields that seem to converge in the writings and views of Graham Harman. In this article, I trace Harman’s view of the philosopher as a promoter and tie the convergence to his understanding of philosophy and its history in general. I then go on to argue that Harman is not driven by self-serving measures but that his promotional efforts are a performative aspect of his own object-oriented philosophy.